Water management in the paddy area in MADA - Baharudin, Siti 'Aisyah; Mohamed Arshad, Fatimah (Malaysian Agricultural Research and Development Institute, 2015)
Water management is an important element in the paddy production. Water management can increase the productivity level, thereby increase the income of farmers. Water management system in MADA is divided into irrigation and drainage. The water storage under irrigation system covers three dams, namely Pedu, Ahning and Muda reservoir. This study examined the weaknesses of irrigation and drainage system in the MADA area. Among the problems are infrastructure density, very tiny road and the distance from the irrigation to the drains. Besides, water control in these areas is insufficient due to high and low paddy field areas. Therefore, several measures were identified to increase the efficiency of water management. Among them are implementation of reticulation system for irrigation and drainage, utilisation of booster and mobile pumps, construction of bunds and good farm practices. Apart from the modernised machines, good water management should be practised by paddy farmers to ensure the efficient use of water.